INTERNAL AUDIT AS A MECHANISM FOR IMPROVING THE EFFICIENCY OF CASH AND LIQUIDITY MANAGEMENT - Aboubakr Saeid Alzineen; Nizar Ramadan; Sohaila G Khalifa (Surman Journal of Science and Technology, 2025)
This study investigates the strategic role of internal audit (IA) in enhancing the efficiency of cash and liquidity management within industrial companies, addressing the critical need for financial stability amidst increasing economic challenges. Specifically, it analyzes how IA functions as a key mechanism for optimizing cash flow, mitigating financial risks, and ensuring regulatory compliance. The research adopts a Descriptive-Analytical approach combined with a case study methodology, focusing on Al-Jayid Food Manufacturing Company. Primary data were collected through semi-structured interviews with financial managers and internal auditors, while secondary data involved the analysis of financial reports and an extensive review of prior academic literature. The findings confirm that a robust internal audit function significantly contributes to enhancing cash management efficiency. IA successfully identified critical liquidity challenges (e.g., a 60-day collection period and short-term payment pressure) and provided actionable recommendations. The implementation of these recommendations led to tangible improvements, including a 25% increase in financial liquidity and a 20% reduction in bad debts. The study also highlights that modern technology (AI and Big Data) adoption, coupled with overcoming key challenges like data inaccuracy and resistance to change, is essential for maximizing IA’s effectiveness.